A non-formaldehyde multi-layer board and a method for manufacturing the same
Patent Information
- Application Number
- CN202611330161.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-31
- Publication Date
- 2026-10-30
AI Technical Summary
然而,这类措施难以在板材全生命周期内持续抑制游离醛的逸出,通常在成品制成后2至6个月,其抑制效果即显著衰退,且无法解决苯酚等其他有毒挥发性组分带来的暴露风险,因而难以满足消费者对全链路无醛健康人居环境的真实需求
本发明采用水性聚氨酯胶粘剂,其主剂(水性聚氨酯乳液,PUD乳液)和固化剂均不含甲醛、苯酚等有害物质,从源头杜绝了有害气体的释放。经测试,本发明多层板的甲醛释放量≤0.005 mg/m3,低于国家ENF级标准限值(≤0.025 mg/m3),且苯酚0检出,实现了全生命周期的绿色环保。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to a formaldehyde-free multilayer board and its preparation method, belonging to the field of engineered wood products technology. Background Technology
[0002] As an important category of engineered wood products, the adhesive system of multilayer boards directly determines the product's mechanical properties, weather resistance, and environmental protection level. Currently, traditional formaldehyde-based adhesives, represented by urea-formaldehyde resin, occupy the majority of the market share due to their cost advantage and mature process compatibility. This system is based on the condensation polymer of urea and formaldehyde, boasting low cost, mature technology, and standardized operating parameters for pressing processes. The remaining small market share consists of phenolic adhesives, soybean adhesives, diphenylmethane diisocyanate (MDI) adhesives, and lignin adhesives. Among these, phenolic adhesives possess excellent strength and water resistance due to the co-condensation structure of phenol and formaldehyde, but their price is relatively high and phenol residue is a significant issue. While bio-based adhesives such as soybean adhesives and lignin adhesives have certain natural source attributes, they suffer from application bottlenecks such as susceptibility to mold growth, insufficient strength, poor system stability, and easy delamination. Although MDI adhesives can achieve truly formaldehyde-free production with low application rates, their high price and the contact toxicity of raw materials during production pose risks to production safety.
[0003] The inherent defects of the aforementioned technical systems have become a bottleneck restricting the upgrading of the multilayer board industry. The primary issue lies in environmental performance: the risk of releasing harmful substances such as free formaldehyde and phenol in urea-formaldehyde and phenol-formaldehyde adhesive systems persists in the long term. Even for some multilayer board products on the market that claim to meet the ENF (Non-formaldehyde added) standard, their technical approach is mostly formula modification in an attempt to reduce formaldehyde release in the short term. However, these measures are difficult to continuously suppress the release of free aldehydes throughout the entire life cycle of the board. Typically, the suppression effect declines significantly 2 to 6 months after the finished product is manufactured, and they cannot solve the exposure risks posed by other toxic volatile components such as phenol. Therefore, they are unable to meet consumers' real demand for a formaldehyde-free and healthy living environment throughout the entire process. Meanwhile, formaldehyde-free adhesive systems struggle to achieve a balance between performance and cost: soybean adhesives cannot meet the requirements for bonding strength and water resistance in load-bearing and humid environments; lignin adhesives are prone to delamination failure due to batch-to-batch instability of raw materials; and MDI adhesives, due to high raw material costs and poor production safety, severely restrict their economic feasibility in large-scale industrial multilayer board production. Furthermore, the fact that cured adhesive layers are invisible makes it difficult for end-users to directly identify the environmental attributes of adhesives, thus weakening the market recognition of green products to some extent. Summary of the Invention
[0004] To address the aforementioned deficiencies in the prior art, this invention provides a formaldehyde-free multilayer board and its preparation method.
[0005] The technical solution of the present invention to solve the above-mentioned technical problems is as follows: In a first aspect, the present invention provides a formaldehyde-free multilayer board, comprising multiple layers of wood veneer, wherein adjacent layers of wood veneer are bonded together by an adhesive layer; the adhesive layer is formed by curing an aqueous polyurethane adhesive. The waterborne polyurethane adhesive comprises a main agent, a curing agent, and a filler; by weight, the waterborne polyurethane adhesive comprises: 100 parts of waterborne polyurethane emulsion; 3-8 parts of curing agent; and 100-150 parts of filler.
[0006] Based on the above technical solution, the present invention can be further improved as follows: Furthermore, the curing agent is an aliphatic diamine curing agent, preferably an aliphatic hexamethylenediamine curing agent.
[0007] Furthermore, the aqueous polyurethane emulsion is an anionic aqueous polyurethane dispersion.
[0008] Furthermore, the filler is selected from one or more of calcium carbonate, talc, or kaolin; the fineness of the filler is 800-1250 mesh.
[0009] Furthermore, the waterborne polyurethane adhesive also includes a corrosion inhibitor, wherein the amount of the corrosion inhibitor added is 0.5 parts by weight to 2 parts by weight, preferably 1 part by weight.
[0010] Furthermore, the adhesive layer is white, and the white adhesive layer is visible on the side of the formaldehyde-free multilayer board.
[0011] Furthermore, the wood veneer is selected from one or more of eucalyptus veneer, poplar veneer, pine veneer or birch veneer; the number of layers in the multi-layer wood veneer is an odd number.
[0012] Furthermore, the formaldehyde emission of the formaldehyde-free multilayer board is ≤0.005 mg / m³. 3 The phenol content was 0; the bonding strength was ≥1.2 MPa; and it did not separate after being boiled in water at 100℃ for 3 hours.
[0013] Secondly, the present invention provides a method for preparing the formaldehyde-free multilayer board as described above, comprising the following steps: S1. Substrate pretreatment: Prepare wood veneer and control its moisture content to 8%-12%; S2. Adhesive preparation: Weigh the waterborne polyurethane emulsion, curing agent and filler according to the formula, mix and stir evenly, and let stand to defoam to obtain waterborne polyurethane adhesive. S3. Applying adhesive: Apply water-based polyurethane adhesive to at least one surface of the wood veneer, with an adhesive application rate of 110 g / m² on each surface. 2 -140g / m2 ; S4. Assembly: The glued wood veneers are symmetrically laid in odd-numbered layers, with the grain direction of adjacent layers perpendicular. S5. Hot pressing: The slab after assembly is hot pressed. The hot pressing temperature is 100℃-135℃, the hot pressing pressure is 1.0MPa-1.5MPa, and the hot pressing time is adjusted according to the slab thickness. S6. Post-processing: The hot-pressed boards are cured, sanded, and cut to obtain the finished product.
[0014] Furthermore, in step S4, the number of wood veneer layers is 5 to 13.
[0015] Furthermore, in step S5, the hot pressing time is 30-40 minutes.
[0016] Furthermore, in step S6, the curing conditions are: temperature 20℃-26℃, relative humidity 35%-55%, and curing time 48-72 hours.
[0017] Compared with the prior art, the present invention has the following beneficial effects: This invention uses a water-based polyurethane adhesive, whose main components (water-based polyurethane emulsion, PUD emulsion) and curing agent are free of harmful substances such as formaldehyde and phenol, thus eliminating the release of harmful gases at the source. Testing shows that the formaldehyde emission of the multilayer board of this invention is ≤0.005 mg / m³. 3 It is below the national ENF level standard limit (≤0.025 mg / m³). 3 Furthermore, phenol was detected at 0%, achieving green and environmentally friendly practices throughout the entire life cycle.
[0018] The water-based polyurethane adhesive used in this invention forms a strong and tough adhesive layer. Its bonding strength can reach 1.2MPa-1.8MPa, which is better than the national standard requirement (≥0.7MPa). At the same time, the adhesive layer has excellent water and heat resistance, and can withstand boiling in water at 100℃ for 3 hours without delamination. Its weather resistance is comparable to phenolic adhesives, which can meet the stringent requirements of high-end application scenarios such as marine boards and outdoor boards.
[0019] This invention, through formulation design, achieves a high proportion of filler (such as calcium carbonate) addition, effectively reducing the adhesive cost per unit area. Comparative tests show that the adhesive cost per sheet of this invention is significantly lower than that of the MDI adhesive system. Simultaneously, the curing agent used in this invention solves the industry problem of short shelf life of traditional MDI curing agents, resulting in a long effective usability time and a wide process window. It is perfectly compatible with existing continuous and automated production lines, possessing strong industrialization and promotion value.
[0020] This invention adds a white inorganic filler (such as calcium carbonate) to the adhesive, resulting in a cured adhesive layer with clear white lines. This feature allows consumers to visually identify the use of the formaldehyde-free adhesive of this invention simply by observing the side of the board, without the need for professional testing tools, greatly enhancing the product's market recognition and consumer trust.
[0021] This invention uses widely available and inexpensive inorganic mineral fillers to replace some of the petrochemical-derived polymer raw materials, thereby reducing the carbon footprint of the product. Detailed Implementation
[0022] The principles and features of the present invention are described below. The examples given are only for explaining the present invention and are not intended to limit the scope of the present invention.
[0023] In the following specific embodiments and comparative examples, unless otherwise specified, the raw materials used are all commercially available, wherein: Eucalyptus veneer: Commercially available, with a moisture content controlled between 8% and 12%.
[0024] PUD Main Agent: Wanhua Chemical Group Co., Ltd., Adwel ® 1620A / B Anionic Waterborne Polyurethane Dispersion.
[0025] Curing agent: Wanhua Chemical Group Co., Ltd., Aquollin ® 180 Aliphatic hexamethylenediamine (HMDA) curing agent.
[0026] Filler: Commercially available industrial-grade calcium carbonate powder, with a fineness of 800 mesh.
[0027] Preservative additives: Commercially available wood preservatives (compliant with BS-1088 standards).
[0028] Example 1 This embodiment provides a formaldehyde-free multilayer board, the preparation method of which is as follows: Substrate pretreatment: Take eucalyptus veneer and use drying equipment to uniformly control its moisture content to 10%.
[0029] Adhesive preparation: By weight, take 100 parts of PUD main agent, 5 parts of HMDA curing agent, 135 parts of 800-mesh calcium carbonate powder, and 1 part of preservative additive. Add the PUD main agent, HMDA curing agent, calcium carbonate powder, and preservative additive in sequence while stirring. Stir at 300 rpm for 20 minutes until evenly dispersed. Let stand for 5 minutes to defoam before use.
[0030] Adhesive application: Use a roller coater to evenly apply the adhesive to the surface of the eucalyptus veneer, with a single-sided adhesive application rate of 125g / m². 2 .
[0031] Assembly: The 7 layers of eucalyptus veneer after gluing are symmetrically assembled in a cross-grain pattern.
[0032] Hot pressing: The slab is fed into a hot press and hot-pressed for 35 minutes at 135℃ and 1.2MPa (18mm slab thickness).
[0033] Post-processing: After hot pressing, the boards are moved to a curing room (23℃, 50% relative humidity) for 72 hours, and then sanded and cut to obtain formaldehyde-free multilayer boards.
[0034] Example 2 This embodiment provides a formaldehyde-free multilayer board, which differs from Embodiment 1 in that the filler content in the adhesive of this embodiment is 100 parts.
[0035] The other raw materials, dosages, and operating procedures are the same as in Example 1, and will not be repeated here.
[0036] Example 3 This embodiment provides a formaldehyde-free multilayer board, which differs from Embodiment 1 in that the filler content in the adhesive of this embodiment is 150 parts.
[0037] The other raw materials, dosages, and operating procedures are the same as in Example 1, and will not be repeated here.
[0038] Example 4 This embodiment provides a formaldehyde-free multilayer board. The difference from Embodiment 1 is that the hot-pressing temperature in this embodiment is 120°C and the hot-pressing time is 30 minutes.
[0039] The other raw materials, dosages, and operating procedures are the same as in Example 1, and will not be repeated here.
[0040] Example 5 This embodiment provides a formaldehyde-free multilayer board, which differs from Embodiment 1 in that the amount of curing agent used in this embodiment is 3 parts.
[0041] The raw materials, dosages, and operating procedures are the same as in Example 1, and will not be repeated here.
[0042] Example 6 This embodiment provides a formaldehyde-free multilayer board, which differs from Embodiment 1 in that the amount of curing agent used in this embodiment is 6 parts.
[0043] The raw materials, dosages, and operating procedures are the same as in Example 1, and will not be repeated here.
[0044] Comparative Example 1 Unlike Example 1, this comparative example uses commercially available soybean gum instead of the PUD adhesive of the present invention, and the rest of the preparation process is the same as that of Example 1.
[0045] Due to the high viscosity of soybean gum, the application rate needs to be increased to 200 g / m² on one side. 2 To ensure even coating.
[0046] Comparative Example 2 Unlike Example 1, this comparative example uses a commercially available MDI curing agent (Wanhua Chemical Group Co., Ltd., CW-20) instead of the HMDA curing agent of the present invention, while the rest of the formulation and process are the same as in Example 1.
[0047] Comparative Example 3 Unlike Example 1, no filler was added in this comparative example, and the amounts of PUD main agent and HMDA curing agent were adjusted to 120 parts and 8 parts, respectively.
[0048] Because no filler was added, the cost of the adhesive layer in this comparative example increased, and the adhesive was not white after curing, so there were no visible adhesive lines on the multilayer board.
[0049] Comparative Example 4 Unlike Example 1, no preservative additives were added to this comparative example.
[0050] The multi-layer board in this comparative example developed mold after being placed outdoors for 6 months.
[0051] Comparative Example 5 The difference from Example 1 is that the filler content in the adhesive of this comparative example is 200 parts.
[0052] The adhesive formulated in this comparative example has poor flowability and is unevenly applied to multilayer boards.
[0053] Comparative Example 6 Unlike Example 1, this comparative example uses commercially available urea-formaldehyde resin instead of the PUD adhesive of the present invention, and the rest of the preparation process is the same as that of Example 1.
[0054] Because urea-formaldehyde resin is used in conjunction with flour, the application rate needs to be increased to 180 g / m² per side. 2 To ensure even coating.
[0055] The multilayer boards prepared in Examples 1-6 and Comparative Examples 1-6 were subjected to performance tests according to GB / T 17657-2013 "Test Methods for Physical and Chemical Properties of Wood-based Panels and Decorative Wood-based Panels" and related standards. The main test items included formaldehyde emission, bonding strength, and peel performance after boiling in water at 100℃. The specific test results are shown in the table below.
[0056] Table 1 Performance test results of the examples and comparative examples
[0057] As shown in Table 1, the formaldehyde-free multilayer boards prepared in Examples 1-6 of this invention are superior to the comparative examples in all key performance indicators. The formaldehyde emission levels in all examples are ≤0.005 mg / m³. 3 It is far below the ENF level standard limit (≤0.025 mg / m³). 3 Furthermore, phenol was not detected, fully verifying the effectiveness of the waterborne polyurethane adhesive system in controlling pollution at its source. The bonding strength generally remained above 1.2 MPa, reaching a maximum of 1.75 MPa, not only meeting national standards but also possessing potential for load-bearing structural applications. Particularly noteworthy is that all examples showed no delamination after boiling in 100°C water for 3 hours, demonstrating excellent water and heat resistance stability, breaking through the performance bottleneck of traditional formaldehyde-free adhesives (such as soybean adhesive) in humid environments.
[0058] Furthermore, the introduction of the preservative significantly enhanced the mold resistance of the board, with no mold growth observed after 6 months of outdoor exposure, while Comparative Example 4, lacking this component, showed significant mold growth under the same conditions. It is noteworthy that filler dosages within the range of 100–150 parts (Examples 2 and 3) maintained good processability and mechanical properties, but exceeding this range (such as 200 parts in Comparative Example 5) led to decreased adhesive flowability and uneven coating, thus affecting the bonding quality, indicating that the formulation window of this invention has a clear optimization boundary.
[0059] In contrast, while Comparative Example 1 (soybean glue) achieved low formaldehyde release, its bonding strength was insufficient (0.5 MPa), it delaminated after boiling and was prone to mold growth; Comparative Example 2 (MDI curing agent), although having acceptable strength, failed the high-temperature boiling test, indicating a defect in its resistance to damp heat; Comparative Example 6 (urea-formaldehyde glue) exceeded formaldehyde release standards, directly contradicting the initial goal of formaldehyde-free production. In summary, this invention, through the synergistic design of waterborne polyurethane emulsion, aliphatic diamine curing agent, and high-fineness inorganic filler, achieves systematic synergistic optimization across multiple dimensions, including environmental friendliness, mechanical properties, durability, cost control, and user identifiability, providing a technologically advanced and economically feasible solution for the industrialization of formaldehyde-free multilayer boards.
[0060] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A formaldehyde-free multilayer board, comprising multiple layers of wood veneer, wherein adjacent layers of wood veneer are bonded together by an adhesive layer; characterized in that, The adhesive layer is formed by curing an aqueous polyurethane adhesive. The waterborne polyurethane adhesive comprises a main agent, a curing agent, and a filler; by weight, the waterborne polyurethane adhesive comprises: 100 parts of waterborne polyurethane emulsion; 3-8 parts of curing agent; and 100-150 parts of filler.
2. The formaldehyde-free multilayer board according to claim 1, characterized in that, The curing agent is an aliphatic diamine curing agent.
3. The formaldehyde-free multilayer board according to claim 1, characterized in that, The aqueous polyurethane emulsion is an anionic aqueous polyurethane dispersion.
4. The formaldehyde-free multilayer board according to claim 1, characterized in that, The filler is selected from one or more of calcium carbonate, talc, or kaolin; the fineness of the filler is 800-1250 mesh.
5. The formaldehyde-free multilayer board according to claim 1, characterized in that, The waterborne polyurethane adhesive also includes a corrosion inhibitor, wherein the amount of the corrosion inhibitor added is 0.5 parts by weight to 2 parts by weight.
6. The formaldehyde-free multilayer board according to claim 1, characterized in that, The adhesive layer is white.
7. The formaldehyde-free multilayer board according to claim 1, characterized in that, The wood veneer is selected from one or more of eucalyptus veneer, poplar veneer, pine veneer or birch veneer; the number of layers in the multi-layer wood veneer is odd.
8. A method for preparing a formaldehyde-free multilayer board as described in any one of claims 1-7, characterized in that, Includes the following steps: S1. Substrate pretreatment: Prepare wood veneer and control its moisture content to 8%-12%; S2. Adhesive preparation: Weigh the waterborne polyurethane emulsion, curing agent and filler according to the formula, mix and stir evenly, and let stand to defoam to obtain waterborne polyurethane adhesive. S3. Applying adhesive: Apply water-based polyurethane adhesive to at least one surface of the wood veneer, with an adhesive application rate of 110 g / m² on each surface. 2 -140g / m 2 ; S4. Assembly: The glued wood veneers are symmetrically laid in odd-numbered layers, with the grain direction of adjacent layers perpendicular. S5. Hot pressing: The slab after assembly is hot pressed at a temperature of 100℃-135℃ and a pressure of 1.0MPa-1.5MPa. S6. Post-processing: The hot-pressed boards are cured, sanded, and cut to obtain the finished product.
9. The method for preparing formaldehyde-free multilayer boards according to claim 8, characterized in that, In step S4, the number of wood veneer layers is 5 to 13; in step S5, the hot pressing time is 30 to 40 minutes.
10. The method for preparing formaldehyde-free multilayer boards according to claim 8, characterized in that, In step S6, the curing conditions are: temperature 20℃-26℃, relative humidity 35%-55%, and curing time 48-72 hours.
